Early age infection of Foot and Mouth Disease affects the reproductive performance in Frieswal males - MATHUR, A K; TYAGI, S; MANDAL, D K (The Indian Journal of Animal Reproduction, 2023)
Semen production performance of adult Frieswal bulls suffered from Foot and Mouth disease infection (FMD) at an early _ age (upto I yr) were compared with bulls of similar age group unaffected by FMD. A significant reduction in the semen donation was evident in bulls suffered with FMD at early age as compared to unaffected bulls of similar age. The mean values of semen quality in terms of volume (3.27±0.19 vs 4.0±0.19 ml) and mass motility (1.6±0.16 vs 2.5±0.10) were significantly lowered in males suffered with Rv!D. Study further revealed that freezable quality semen could only be obtained from only 20% of bulls suffered from FMD as compared to 73% in non affected group. These findings indicate that FMD infection at early age (upto I yr) affects the future semen production performance in Frieswal bulls.